Empirical Testing of Month of the Year Effect on Selected Commercial Banks and Services Sector Companies Listed on Bahrain Bourse - Hawaldar, Iqbal Thonse; B., Shakila; Pinto, Prakash (International Journal of Economics and Financial Issues, 2017)
In financial literature we find numerous studies examining the presence of diverse types of calendar anomalies in different stock exchanges of the world. The current paper aims to investigate the month of the year effect in randomly selected ten companies from banking sector and service sector traded on the Bahrain Bourse for a period of five years commencing from 1st January 2010 to 31st December 2014. The empirical research was conducted using descriptive statistics and Kruskal-Wallis H Test. The findings of the study revealed that none of the companies selected for the study exhibited significant monthly returns for the study period except Bahrain Maritime & Mercantile International (BMMI). The paper suggests that the absence of said calendar anomaly may be due to thin trading practiced in the Bahrain Stock Exchange. Keywords: Calendar Anomalies, Month of the Year Effect, Bahrain Stock Exchange, Descriptive Statistics and Kruskal-Wallis H Test, Thin Trading. JEL Classifications: G10, G14, G15